On experimental investigation of the web-based stock-exchange model - Mockus, Jonas; Katin, Igor; Katina, Joana (Lietuvos matematikos rinkinys, 2012)
In this paper, the updated model USEGM simulating the stock exchange is investigated. The updated model includes the transaction costs to reflect the reality better. To represent users that prefer linear utility functions, USEGM adds the new models which minimize absolute prediction errors to the traditional ones minimizing square deviations. However, the main objective of USEGM is not forecasting, but simulation of financial time series that are affected by predictions of the participants. The model has been compared with actual financial time series.